Anorthosite (Lunar Rock Replicant) - An Anti-Cancerous Medicinal Approach for H460: Human Lung Cancer with Validation via ROS Anti-Oxidant Analysis (AYUSHDHARA, 2023)
Anorthosite, a commonly occurring mineral found in lunar regolith, holds the promise of a groundbreaking dual application in the fields of cancer therapy and space medicine.In the context of lung cancer therapy, anorthosite nanoparticles were synthesized and subjected to MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay along with FTIR to assess their cytotoxic effects on H460 lung cancer cells. The results revealed that anorthosite nanoparticles exhibit a dose-dependent cytotoxic effect on H460 cells, suggesting their potential as a novel treatment modality for lung cancer with Inhibitory Concentration IC50 value at 50% to be 21.65 which simply gestures of how toxic it could be if being treated as a cancer drug via chemo/immune/radio or target cell therapies, even when merged with ayurvedic discipline. These findings warrant further investigations into the precise mechanisms of anorthosite-mediated cytotoxicity and its therapeutic potential in vivo.Moreover, anorthosite's role in space medicine was explored by assessing its ability to mitigate oxidative stress, a major concern for astronauts exposed to the harsh space environment. Reactive oxygen species (ROS) generated during space travel can have detrimental effects on an astronaut's health. Anorthosite nanoparticles were tested for their capacity to scavenge ROS in an in vitro model. The results demonstrated that anorthosite nanoparticles possess potent antioxidant properties, indicating their potential in safeguarding astronauts from oxidative stress-induced health issues during prolonged space missions.This dual-application research on anorthosite nanoparticles highlights their therapeutic potential for lung cancer treatment and their utility in protecting astronauts from oxidative stress in space.